SWOT analysis of the current situation of medical physicists in Portugal. (September 2016) - Figueira, R.; Poli, E.; Isidoro, J.
Abstract : Introduction: During 2015 DFM-SPF (Medical Physics Division of the Portuguese Physics Society) conducted a survey for the characterization of the Medical Physics situation in Portugal. Among other questions participants were asked to identify the Strengths, Weaknesses, Opportunities and Threats (SWOT) of the profession. Purpose: The purpose was to conduct a SWOT analysis of the current situation of Medical Physics in Portugal contributing for the strategic development of the profession and for the identification of potential actions to be taken to improve the situation. Materials and methods: Based on the responses from 83 portuguese medical physicists, a SWOT matrix was created to identify common Strengths, Weaknesses, Opportunities and Threats. The analysis was directed to design appropriate actions that could successfully lead to strategic outcomes. Results: The most commonly identified Strengths were the dedication, commitment and competence of the professionals. The Weaknesses were the lack of professional recognition/regulation and, the lack of training/qualification of new professionals. As Opportunities, the most frequently mentioned were the implementation of the new BSS directive and the growing need for medical physicists due to new installations. The pressure from other professionals like radiographers or biomedical engineers sometimes employed to perform medical physicist's tasks, the coming of foreigners with recognized qualifications and the unclear legislation, were the main Threats mentioned. Conclusion: A SWOT analysis has been employed with success and in this case was a useful tool in providing guidance to the portuguese medical physicists to develop a strategic action plan to improve the current situation. Disclosure: The authors have nothing to disclose.